SECTORAL ROLE ANALYSIS TO STRENGTHEN THE ECONOMIC STRUCTURE (CASE STUDY OF BIMA CITY-WEST NUSA TENGGARA) - Fajrin Hardinandar; Ahmad Sandi; Sitaman Said; Suaeb Suaeb (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2021)
The sectoral contribution of Bima City is very weak towards the economic structure in West Nusa Tenggara Province. The purpose of this study is to increase sectoral strength in the City of Bima and see how it contributes to performance at the provincial level. The results showed the primary sector which actually produced a decline in the City of Bima along with the industrial sector and some service sectors. All sectors in the City of Bima are still in the backward category. The sectoral contribution of Bima City is still very weak to sustain growth at the provincial level. An important finding from this study is that Bima City has a strong economic structure due to the development of the base sector, but the small number of population is sufficient to determine the number of output requests and sectoral contributions of Bima City to the economic structure at the provincial level. Perhaps the base sectors could increase the economic growth of the City of Bima but was less successful in growing growth at the provincial level.